1950
DOI: 10.1111/j.1744-7348.1950.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Powdery Mildew Investigations

Abstract: The development of Eryszphe graminis f. tritici Em. Marchal, from spore germination to spore formation, occupied 6 days and ascospore discharge in the field covered a period of I month. On immune hosts development of the fungus generally ceased at the point of invasion of cell cytoplasm. The features of host plant resistance have been discussed.Lithium chloride soil applications were made as 0.8% solution in glasshouse seedling plant experiments and at 56 lb./acre rate in a factorial field trial. In the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1954
1954
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Susceptibility requires, there fore, a more exacting correspondence between host and parasite genes than does resistance, since the plant is resistant either by virtue of its own genes for resistance or, alternatively, through lack of any one of the genes for virulence in the para�ite. These findings correspond with the general observation that susceptibility to a given parasite is the exceptional, resistance the more wide spread property (4,18,19). They imply that susceptibility results from an in teraction between specific gene products of the host and of the parasite and are in accord with the view that susceptibility is a positive attribute of the host and not dependent solely on the initial absence of materials toxic to the fungus (20) .…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Susceptibility requires, there fore, a more exacting correspondence between host and parasite genes than does resistance, since the plant is resistant either by virtue of its own genes for resistance or, alternatively, through lack of any one of the genes for virulence in the para�ite. These findings correspond with the general observation that susceptibility to a given parasite is the exceptional, resistance the more wide spread property (4,18,19). They imply that susceptibility results from an in teraction between specific gene products of the host and of the parasite and are in accord with the view that susceptibility is a positive attribute of the host and not dependent solely on the initial absence of materials toxic to the fungus (20) .…”
supporting
confidence: 87%
“…Wortley's report that the failure of <IIl ildew to de velop on plants grown in soil with lithium was due to failure to penetrate the cellulose wall (62) has been confirmed by Smith & Blair (19). Kent (63) found an inverse correlation between lithium content of the leaves and mildew intensity, but he left open the question of whether the effects of lithium were direct or through a modification of host physiology.…”
Section: Effect Of Host Environment On Development Of the Parasitementioning
confidence: 81%
See 1 more Smart Citation
“…The use of wide RS has been reported to increase PM severity (Broscious et al 1985), while the use of high SR has been reporred both to increase (Smith and Blair 1950) (Tompkins 1990;Tompkins et al l99la,b). (Hammet and Manners 1971).…”
mentioning
confidence: 99%
“…Earlier researchers demonstrated histochemical modification of cell walls at the penetration site by this fungus and suggested that it could release cell wall-degrading enzymes from appressoria (Akai et al 1968;Carver et al 1998;Ghemawat 1977;Smith and Blair 1950;Staub et al 1974;Suzuki et al 1999). Fric and Wolf (1994), Pascholati et al (1992), and Suzuki et al (1999) proved release of cutinase, cellulase, and pectinase by B. graminis on artificial membranes.…”
Section: Introductionmentioning
confidence: 97%